Copper excess in liver HepG2 cells interferes with apoptosis and lipid metabolic signaling at the protein level - Liu, Yu; Yang, Huarong; Song, Zhi; Gu, Shaojuan (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Copper is an essential trace element that serves as an important catalytic cofactor for cuproenzymes, carrying out major biological functions in growth and development. Although Wilson’s disease (WD) is unquestionably caused by mutations in the ATP7B gene and subsequent copper overload, the precise role of copper in inducing pathological changes remains poorly understood. Materials and Methods: Our study aimed to explore, in HepG2 cells exposed to copper, the cell viability and apoptotic cells was tested by MTT and Hoechst 33342 stainning respectively, and the signaling pathways involved in oxidative stress response, apoptosis and lipid metabolism were determined by real time RT-PCR and Western blot analysis. Results: The results demonstrate dose- and time-dependent cell viability and apoptosis in HepG2 cells following treatment with 10μM , 200μM and 500μM of copper sulfate for 8 and 24 h. Copper overload significantly induced the expression of HSPA1A (heat shock 70kDa protein 1A), an oxidative stress-responsive signal gene, and BAG3 (BCL2 associated athanogene3), an anti-apoptotic gene, while expression of HMGCR (3-hydroxy-3-methylglutaryl-CoA reductase), a lipid biosynthesis and lipid metabolism gene, was inhibited. Conclusion: These findings provide new insights into possible mechanisms accounting for the development of liver apoptosis and steatosis in the early stages of Wilson’s disease.